2008
DOI: 10.1086/588028
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Separate Star‐forming from AGN Galaxies at Intermediate Redshift: The Submillijansky Radio Population in the VLA‐COSMOS Survey

Abstract: We explore the properties of the submillijansky radio population at 20 cm by applying a newly developed optical color-based method to separate star forming (SF) from AGN galaxies at intermediate redshifts (z 1.3). Although optical rest-frame colors are used, our separation method is shown to be efficient, and not biased against dusty starburst galaxies. This classification method has been calibrated and tested on a local radio selected optical sample. Given accurate multi-band photometry and redshifts, it carr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 90 publications
1
52
0
Order By: Relevance
“…In an attempt to determine the spectral type of the 12 galaxies in our sample for which we lack optical spectra, we make use of a photometric (rest-frame color based) method extensively studied in Smolčić et al (2008). Smolčić et al (2006) have shown that principal component rest-frame colors (P1 and P2 hereafter) drawn from the modified Strömgren photometric system (3500-5800 Å; Odell et al 2002) essentially trace the position of a galaxy in the BPT diagram (Baldwin et al 1981;Kewley et al 2001Kewley et al , 2006Kauffmann et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In an attempt to determine the spectral type of the 12 galaxies in our sample for which we lack optical spectra, we make use of a photometric (rest-frame color based) method extensively studied in Smolčić et al (2008). Smolčić et al (2006) have shown that principal component rest-frame colors (P1 and P2 hereafter) drawn from the modified Strömgren photometric system (3500-5800 Å; Odell et al 2002) essentially trace the position of a galaxy in the BPT diagram (Baldwin et al 1981;Kewley et al 2001Kewley et al , 2006Kauffmann et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Smolčić et al (2006) have shown that principal component rest-frame colors (P1 and P2 hereafter) drawn from the modified Strömgren photometric system (3500-5800 Å; Odell et al 2002) essentially trace the position of a galaxy in the BPT diagram (Baldwin et al 1981;Kewley et al 2001Kewley et al , 2006Kauffmann et al 2003). Hence, they can be used as efficient tracers of galaxy type, such as low-luminosity AGN (Seyfert and LINER), star forming, and composite galaxies (see Smolčić et al 2006Smolčić et al , 2008 for more details). Here, we extend the method developed by Smolčić et al (2008), that utilizes only the P1 color to disentangle star forming from AGN galaxies, to a probabilistic approach that uses both, P1 and P2 colors, and we adapt it to an IR-(rather than radio-) selected sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations